STRATEGI KERJA SAMA KEAMANAN MARITIM INDONESIA-JEPANG DALAM PENANGANAN ILLEGAL, UNREPORTED, AND UNREGULATED FISHING DI INDONESIA - Asdiarti, Riwana; Abdullah, Nurjannah (Jurnal Ilmiah Hubungan Internasional Fajar, 2023)
Illegal, Unreported, and Unregulated Fishing has brought Indonesia to a very disadvantaged condition from the economic and social aspects. IUU Fishing not only affects Indonesia, but it also to countries that have interests in Indonesia's maritime territory given that its activities are cross-border crimes. Indonesia has conducted various co-operations as an effort to deal with the issue of IUU Fishing. Through this research, the steps taken by Indonesia is to cooperate with Japan using several strategies. This research uses a qualitative method with library research to analyse the cooperative relationship between the two countries, and uses the conceptual framework of maritime security and international cooperation theory to deepen the understanding of the issue. Thenresearch results show several strategies of cooperation between Indonesia and Japan through information exchange in the forum (IJMF), grant aid, and the use of technology to deal with IUU Fishing in Indonesia. However, Indonesia and Japan must face challenges in implementing the cooperation strategies that have been implemented. This is due to geographical challenges due to Indonesia's vast maritime territory, the COVID-19 Pandemic and internal issues related to Indonesia's governance that add to the complexity of the problem.